Pengaruh Pasar Tradisional Terhadap Arus Lalu Lintas - Muhammad Chaiddir Hajia (Universitas Nusantara PGRI Kediri, 2022)
On the island of Sulawesi, there is an area called Buton Regency which is located on the largest island outside Sulawesi, namely Buton Island. The capital of the archipelago is in Pasarwajo (Pasarwajo). Pasarwajo (Pasarwajo) which is one of the sub-districts in Buton Regency, Southeast Sulawesi, has developed economically and socially, but also in the form of utilization of urban space. This research is first conducted to identify traffic problems in Sabho Market from the identification and formulation stages of the problem, then proceed with a traffic survey to see the existing condition of the road and get the traffic volume. After completing the survey, the final stage is data processing to obtain traffic volume using the 1997 MKJI method. This research was conducted for 3 days starting from 06.00 – 15.00 WITA with the research time interval being taken for 15 minutes and the type of road is 2/2 UD. . From the results of research and discussions that have been carried out, it is found that traffic behavior for Jalan Anoa, Baubau City with the type of road 2 lanes 2 directions (2/2 UD), the category of inner city roads, has a type B road service level with a traffic volume of 819, 4 smp/hour using the 1997 MKJI method and 819.4 cur.